2014
DOI: 10.1093/icvts/ivu062
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selective pulmonary perfusion on the inflammatory response and clinical outcome of patients with chronic obstructive pulmonary disease undergoing cardiopulmonary bypass

Abstract: These results indicate a non-significant trend that repeated hypothermic lung perfusion with venous blood during CPB may have a protective effect on the lungs. A multicentre study design and larger cohort seem necessary to demonstrate the benefits of sPP more clearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…As reported in animal studies, [13][14][15][16] small randomised trials and observational studies in infants 18 19 and adults, [22][23][24][25] we have now evaluated and confirmed in a clinical setting with adult patients with COPD, that pulmonary artery perfusion with oxygenated blood during CPB results in a higher postoperative oxygenation. This was obtained without an increased incidence of complications or significant prolongation of the surgical procedure.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…As reported in animal studies, [13][14][15][16] small randomised trials and observational studies in infants 18 19 and adults, [22][23][24][25] we have now evaluated and confirmed in a clinical setting with adult patients with COPD, that pulmonary artery perfusion with oxygenated blood during CPB results in a higher postoperative oxygenation. This was obtained without an increased incidence of complications or significant prolongation of the surgical procedure.…”
Section: Discussionsupporting
confidence: 53%
“…It has now been confirmed in several animal models that bronchial artery blood flow is decreased substantially during CPB, and although exposure to CPB alone is enough to cause pulmonary injury, concomitant cessation of pulmonary artery flow contributes significantly to the development of postoperative pulmonary dysfunction. [9][10][11][12] The results of animals studies, [13][14][15][16] small randomised trials in infants with congenital heart disease 17-20 and inconclusive minor randomised trials and observational studies in adults [21][22][23][24][25] indicates that pulmonary artery perfusion with normothermic oxygenated blood preserves postoperative oxygenation. Further, lung transplantation experiences has shown that pulmonary artery perfusion with a hypothermic preservation solution protects the lungs from warm ischaemic injury during storage and transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Selective continuous pulmonary artery perfusion flows of 7 ml/kg/min, comparable to those used in our study, in low-risk adult patients during on-bypass coronary revascularization resulted in no significant clinical benefits (14, 15) despite slightly improved pulmonary perfusion indices and decreased pulmonary tissue inflammatory cytokine production. Importantly, Kiessling et al (5) reported an absence of clinical benefits despite small trends toward decreased pulmonary tissue-generated inflammatory markers in a study of intermittent selective pulmonary perfusion in high-risk pulmonary patients undergoing on-bypass coronary revascularization. Similar to our results, the latter study demonstrated a statistically insignificant unfavorable trend toward increased overall mortality and pulmonary morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Even such well-established concepts as the deleterious effects of inflammatory cytokines still await their correlation with specific clinical end-points. While Siepe et al (20) attributed the protective effects of pulmonary perfusion during CPB to the decreased pulmonary tissue expression and blood concentration of inflammatory cytokines, such as IL-6, IL-8, IL-10, and TNF-α, and others (5, 15, 19) could not reproduce these effects. Likewise, despite avoidance of CPB, pulmonary atelectasis and activation of inflammatory cascades associated with pulmonary ischemia–reperfusion injury, off-bypass technique of coronary revascularization offers only a modest clinical impact on pulmonary outcomes in patients with severe pulmonary disease (2123).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pulmonary artery perfusion during CPB can be effective in reducing postoperative right ventricular dysfunction in high-risk patients undergoing LVAD placement [ 80 ]. The translation of such changes into better clinical outcomes remains unclear and may be restricted to selective group of patients as demonstrated by a recent trial in patients with COPD undergoing cardiac surgery using CPB where no significant protective effect on lungs was documented [ 81 ].…”
Section: Pulmonary Protection Strategiesmentioning
confidence: 99%